Analisis Lapisan Aluminium Pada Permukaan Baja Dengan Metode Twin-Wire Arc Spray Terhadap Laju Korosi - Fahrezi, Wibi Adrian; ., Nurhadi; Hastuti, Sri; Pramono, Catur; Nurdin, Akhmad; Wibowo, Rheza Ari; Al Hassany, Ibnu Rosyid; Pandupradityo, Bramono (Rekayasa Material, Manufaktur dan Energi, 2024)
Electrical twin-wire arc spray is often used as protection from material components. The coating process aims to protect the coating from environmental disturbances. The quality of the coating yield is indicated by corrosion resistance. The spraying distance in the thermal spray process will affect the corrosion rate, morphological structure, and thickness. The purpose of this study is to analyze the effect of distance variations in the electrical twin-wire arc spray process with an aluminum coating on corrosion rate, morphological structure, and layer thickness in AISI 1020 steel. Tests are carried out for corrosion tests, scanning electron microscope (SEM), and layer thickness. The implementation of the study used experimental methods using distance variations of 150 mm, 250 mm, and 350 mm. The results of the study of the lowest corrosion rate value at a distance of 150 mm are included in the good category with a value of 0.13667 mmpy, the morphological structure of the layer using a closer distance obtains a smooth and dense layer, then for the highest layer thickness at a distance of 150 mm with an average of 317.16 μm.